Growth Arrest Specific Gene 6 Protein Concentration in Cerebrospinal Fluid Correlates with Relapse Severity in Multiple Sclerosis. (27th May 2013) - Sainaghi, P. P.; Collimedaglia, L.; Alciato, F.; Molinari, R.; Sola, D.; Ranza, E.; Naldi, P.; Monaco, F.; Leone, M.; Pirisi, M.; Avanzi, G. C.
Abstract : Background . Growth arrest specific gene 6 (Gas6) protein enhances survival of oligodendrocytes and neurons, and it is involved in autoimmunity. Therefore, we aimed to verify whether cerebrospinal-fluid (CSF) Gas6 concentration may represent a biomarker of disease activity in multiple sclerosis. Methods . Sixty-five patients who underwent a spinal tap during relapse of relapsing/remitting multiple sclerosis (RR-MS)(McDonald-criteria) were studied. Forty patients affected by noninflammatory/nonautoimmune neurological diseases served as controls. Relapse was defined according to Schumacher criteria. Symptoms were grouped according to Kurtzke-Functional System (FS). Clinical characteristics of the relapse, duration, Expanded-Disability-Status Scale (EDSS) change, number of FS involved, completeness of recovery, age, steroid therapy, were categorised. Patients were followed at 6-month intervals to assess relapse rate and EDSS progression. Gas6 was measured (CSF, plasma) by in-house-enzyme-linked immunoassay (ELISA). Results . Higher CSF Gas6 concentrations were observed in relapses lasting ≤60 days (8.7 ± 3.9 ng/mL) versus >60 days (6.5 ± 2.6) or controls (6.5 ± 2.4; P = 0.05 ), with ≤2 FS involved (8.5 ± 3.8) versus >2 FS (5.6 ± 2.5) (P < 0.05 ) and EDSS change ≤2.5 points (8.8 ± 3.7) versus >2.5 (6.5 ± 3.5) (P = 0.04 ). Conversely, CSF Gas6 was not predictive of the completeness of recovery. Plasma and CSF concentrations were not related (R 2 = 0.0003 ), and neither were predictive of relapse rate or EDSS progression after first relapse. Conclusions . CSF concentration of Gas6 is inversely correlated with the severity of relapse in RR-MS patients but does not predict the subsequent course of the disease.